Amiselimod, a sphingosine 1-phosphate receptor-1 modulator, for systemic lupus erythematosus: A multicenter, open-label exploratory study. (December 2020) - Tanaka, Yoshiya; Kondo, Kazuoki; Ichibori, Ayako; Yanai, Yoshiari; Susuta, Yutaka; Inoue, Shinsuke; Takeuchi, Tsutomu
Objective: To evaluate the safety, pharmacokinetics, pharmacodynamics, and exploratory efficacy of amiselimod, an oral selective sphingosine 1-phosphate receptor-1 modulator, in patients with systemic lupus erythematosus (SLE). Methods: A multicenter, open-label phase Ib trial was conducted in Japan. Patients in Part 1 and Part 2-B received 0.2 mg amiselimod while those in Part 2-A received 0.4 mg amiselimod for 24 weeks. Results: Seventeen subjects received 0.2 or 0.4 mg amiselimod. Amiselimod and amiselimod-P plasma concentrations increased dose-dependently. Peripheral blood lymphocyte count decreased in all patients after amiselimod treatment, with no clear dose response. There were no serious/severe adverse events (AEs) or clinically meaningful cardiac effects. Five subjects were withdrawn from amiselimod treatment following a decrease in lymphocyte count to <200/μl. Anti-double stranded-DNA antibody decreased from baseline to Week 24/end of treatment (EOT), with those in 2 subjects (22.2%) decreasing to within the normal range. Total SLE disease activity index 2000 score decreased by ≥4 at EOT in 7 of 17 subjects. Conclusions: Amiselimod was generally well tolerated. While no serious AEs or infectious AEs led to discontinuation, low lymphocyte counts of <200/μl were observed as a laboratory abnormality. Our findings suggest the potential efficacy of amiselimod for patients with SLE. Trial registration: ClinicalTrials.gov identifier: NCT02307643.